Peningkatan Awareness Masyarakat tentang Penatalaksanaan Kegawatan Hipertensi melalui Edukasi Kesehatan di Wilayah Kerja Puskesmas Kota Ruteng - Novita Ana Anggraini; Godefridus Antoni Turut (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Hypertension remains one of the leading non-communicable diseases and is a major public health concern due to its high prevalence and the low level of community awareness regarding its management. Community assessment conducted in the working area of Puskesmas Kota Ruteng identified hypertension as the highest-ranking health problem, highlighting the need for effective community-based health promotion interventions. Objective: This community service aimed to increase public awareness regarding hypertension management through structured health education in the working area of Puskesmas Kota Ruteng. Method: This community service adopted a community nursing approach consisting of community assessment, problem identification using Fishbone Analysis, priority setting using the Urgency, Seriousness, and Growth (USG) method, and strategic planning through SWOT Analysis. The selected intervention was implemented through health education using lectures, interactive discussions, question-and-answer sessions, blood pressure screening, and leaflet distribution targeting adults, patients with hypertension, family members, and community health volunteers. Result: Community assessment identified 1,113 hypertension cases during the December 2025–May 2026 period, consisting of 439 male and 694 female patients. Baseline findings also showed that 70% of community members rarely exercised, 60% frequently consumed high-salt foods, and 55% did not routinely monitor their blood pressure. Following the educational intervention, ≥80% of participants demonstrated improved knowledge and correctly answered the evaluation questions. Participants also showed better understanding of routine blood pressure monitoring, medication adherence, healthy lifestyle practices, and hypertension prevention, reflecting improved awareness of hypertension management. Conclusion: Community-based health education developed through systematic problem analysis using Fishbone, USG, and SWOT effectively improved public awareness regarding hypertension management. This approach may serve as a sustainable strategy to strengthen community participation in hypertension prevention and control at the primary healthcare level. Keywords: community awareness, Fishbone analysis, health education, hypertension, SWOT analysis, USG.